Inactivation of photosynthetic cyclic electron transports upregulates photorespiration for compensation of efficient photosynthesis in Arabidopsis - Chen, Qi; Lan, Yixin; Li, Qinghua; Kong, Mengmeng; Mi, Hualing (Frontiers in Plant Science, 2023)
Plants have multiple mechanisms to maintain efficient photosynthesis. Photosynthetic cyclic electron transports around photosystem I (CET), which includes the PGR5/PGRL1- and NDH- pathways, and photorespiration play a crucial role in photosynthetic efficiency. However, how these two mechanisms functionally link is not clear. In this study, we revealed the photorespiration could compensate the function of CET in efficient photosynthesis by comparison of the growth phenotypes, photosynthetic properties, and photorespiratory activity between the mutants deleted PGR5 or PGRL1 under NDH defective background (pgr5 crr2 or pgrl1a1b crr2). Both CET mutants pgr5 crr2 and pgrl1a1b crr2 displayed similar suppression effect on photosynthetic capacities of light reaction, and growth phenotypes under low light conditions. However, the total CET activity and photosynthetic oxygen evolution of pgr5 crr2 were evident lower than pgrl1a1b crr2, accompanying with the up-regulation of photo-respiratory activity under low light conditions, resulting in severe suppression of photosynthetic capacities of light reaction, and finally photodamaged phenotype under high light or fluctuating light conditions. Based on these findings, we suggests that photorespiration compensates the loss of CET functions in regulation of photosynthesis and that coordination of both mechanisms is essential for maintaining efficient operation of photosynthesis, especially under stressed conditions.